Mechanical durability of superhydrophobic surfaces: the role of surface modification technologies - Zhi, Jing-Hui; Zhang, Li-Zhi; Yan, Yuying; Zhu, Jie (Elsevier, 2017)
Various surface modification technologies have been used to develop superhydrophobic surface, however their durability has been recognized as the major obstacle for the real applications. Here a quantitative investigation was conducted to evaluate the effects of different surface modification methods on the surfaces’ mechanical durability. The superhydrophobic surfaces were prepared by the combination of two surface roughing methods (etching and sandblasting) with chemical modifications with four low surface energy materials: silica sol (SS), octadecanoic acid (OA), heptadecafluoro-1,1,2,2-tetrahydrodecyltrichlorosilane (HDFS) and hexadecyltriethoxysilane (HTS). XPS was used to analyze the elements composition and AFM was used to measure the roughness of the surfaces. The durability of these surfaces was tested by a sandpaper abrasion experiment. The collective results showed that the low surface energy materials had significant effects on the surface roughness, which would then play an important role in the durability of these rough surfaces. The SS modified rough surfaces possessed higher roughness and better durability than the surfaces modified by other three low surface energy materials. SS modified rough surfaces could bear 60 cycles of abrasion with 10 g weights on 1500 CW sandpaper.